Atrial fibrillation in heart failure: the chicken or the egg?. Issue 7 (16th July 2008) - Balasubramaniam, R; Kistler, P M
Abstract : Atrial fibrillation (AF) and heart failure (HF) are the emerging epidemics of cardiovascular disease in the new millennium. Both are responsible for considerable morbidity and mortality and health budget expenditure. The advent of catheter ablation for patients with AF has provided important new insights into the relative contribution of AF to left ventricular dysfunction. The aim of this review is to discuss the complex interplay in the pathophysiology of AF and HF to improve our understanding of the basis for current treatment strategies and guide future research direction.